Genome-Wide Analysis of the GRAS Gene Family and Functional Identification of GmGRAS37 in Drought and Salt Tolerance - Wang, Ting-Ting; Yu, Tai-Fei; Fu, Jin-Dong; Su, Hong-Gang; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Guo, Jun; Ma, You-Zhi; Wei, Wen-Liang; Xu, Zhao-Shi (Frontiers in Plant Science, 2020)
GRAS genes, which form a plant-specific transcription factor family, play an important role in plant growth and development and stress responses. However, the functions of GRAS genes in soybean (Glycine max) remain largely unknown. Here, 117 GRAS genes distributed on 20 chromosomes were identified in the soybean genome and were classified into 11 subfamilies. Of the soybean GRAS genes, 80.34% did not have intron insertions, and 54 pairs of genes accounted for 88.52% of duplication events (61 pairs). RNA-seq analysis demonstrated that most GmGRASs were expressed in 14 different soybean tissues examined and responded to multiple abiotic stresses. Results from quantitative real-time PCR analysis of six selected GmGRASs suggested that GmGRAS37 was signiﬁcantly upregulated under drought and salt stress conditions and abscisic acid and brassinosteroid treatment; therefore, this gene was selected for further study. Subcellular localization analysis revealed that the GmGRAS37 protein was located in the plasma membrane, nucleus, and cytosol. Soybean hairy roots overexpressing GmGRAS37 had improved resistance to drought and salt stresses. In addition, these roots showed increased transcript levels of several drought- and salt-related genes. The results of this study provide the basis for comprehensive analysis of GRAS genes and insight into the abiotic stress response mechanism in soybean.